Pengaruh Integrasi Rantai Pasokan terhadap Kinerja Organisasi Nirlaba: Peran Mediasi Praktik Rantai Pasokan Berkelanjutan dan Moderasi Tantangan Rantai Pasok Pada LAZNAS Al-Irsyad di Jawa Barat - Keanu Mikhael Driki Taslim; Wahyuningsih Wahyuningsih; Ratna Darasih (Jurnal Simki Economic, 2026)
This study investigates the impact of supply chain integration on the performance of non-profit organizations, taking into account the mediating effect of sustainable supply chain practices and the moderating role of supply chain challenges. The research focuses on religious-based social organizations engaged in social services and humanitarian assistance. An explanatory quantitative design was employed, utilizing the Partial Least Squares Structural Equation Modeling technique to analyze causal relationships among the variables. Data were obtained through questionnaires distributed to managers of non-profit organizations located in West Java using a purposive sampling method. The research sample consisted of 153 managers of LAZNAS Al-Irsyad. The findings indicate that supply chain integration significantly influences organizational performance, both directly and indirectly through sustainable supply chain practices as a mediating factor. However, supply chain challenges were not found to significantly moderate the relationship between sustainability practices and organizational performance. These results emphasize the importance of process integration and operational sustainability in enhancing organizational effectiveness and strengthening public trust in non-profit organizations. Furthermore, this study contributes both theoretically and practically to the advancement of supply chain management literature within the non-profit sector, while underscoring the necessity for integrated managerial approaches to address the dynamic and complex operational conditions faced by social organizations.